Rediscovery of Smilax turbans (Smilacaceae) from Arunachal Pradesh, India, after 95 years of type collection - Sukhramani, Geetika; Choudhary, Ritesh Kumar (Phytotaxa, 2023)
Smilax turbans, an endemic species from Arunachal Pradesh, India, was last collected in 1928 by F. Kingdon-Ward, has not been collected since then. During our recent fieldwork, we found a population in Kurung Kumey district, about 500 km from the presumable type collection, after more than 95 years of its last known collection. To facilitate its identification, eventual conservation, we present a detailed description, illustrations, field, microscopic images, distribution, phenology, comparison with closely related species.